Preliminary Findings on Social Networks of American Indian Parents Participating in a Family Based Substance Use Prevention Program with their Children. - Tuitt, Nicole R.; Ivanich, Jerreed; Mousseau, Alicia C.; Schultz, Katie; Keane, Ellen; Asdigian, Nancy; Whitesell, Nancy (Journal of Child & Family Studies, 2023)
Evidence of early initiation of substance use among American Indian youth and links between early initiation and substance use disorder make prevention imperative. The Thiwáhe Gluwáš'akapi Program (TG, Sacred home in which family is made strong) is a group-based and family-centered intervention that was culturally adapted from the Strengthening Families Program for Parents and Youth 10–14 to address this need. Groups of families participated in TG together for seven weeks; this study explored whether the social networks of parents participating in this program were enhanced through this group experience, particularly with regard to connections that support parenting. Parents completed social network surveys at baseline and post-intervention (n = 106) that included questions about who they would go to when they experienced challenges in parenting their children. Average network centrality and desire to seek parenting advice from TG program peers both increased at post-test. The findings from this preliminary study suggest that group-based interventions have the potential to impact social networks and point to the need for rigorous study of how networks are influenced by such interventions and, in turn, may affect their impact. Highlights: Social networks as a lever for substance use prevention for American Indian youth. Interdependent systems often typify American Indian tribal-based communities. Social network analysis as a tool for examining group-based prevention programs.